Pětipodlažní železobetonová nosná konstrukce administrativní budovy - Večeřa, František (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Diplomová práce se zabývá návrhem nosné konstrukce administrativní budovy. Jde o novostavbu, která je umístěná v městě Brně. Stavba je řešena jako železobetonový skelet se ztužujícím jádrem. Stavba má pět nadzemních podlaží. Práce je zaměřena na návrh a statické posouzení vybraných částí budovy. Součástí je výkresová dokumentace.

Diploma thesis deals with the design of a carrier structure of an administrative building. It is a new building, which is located in the city of Brno. The building is solved as a reinforced concrete skeleton with stiffening core. There ares five overground floors. Thesis is focused on the design and the static assessment of selected parts of the building. It includes a drawing documentation.
Reinforced concrete structure of a administrative building
Keywords: Administrativní budova; železobeton; lokálně podepřená železobetonová deska; schodiště; sloup; základová patka; zatížení; vnitřní síly; dimenzování.; Administrative building; reinforced concrete; locally supported reinforced concrete slab; staircase; column; footing; load; internal forces; dimensioning.